Depressive Symptoms and Cognitive Decline Among Chinese Rural Elderly Individuals: A Longitudinal Study With 2-Year Follow-Up - Zhou, Shuai; Wang, Qiong; Zhang, Jingya; Wang, Qing; Hou, Fangfang; Han, Xiao; Hu, Shilian; Shen, Guodong; Zhang, Yan (Frontiers in Public Health, 2022)
Background Depressive symptoms and mild cognitive impairment (MCI) are highly prevalent in rural China. The study aimed to investigate the longitudinal associations between changes in depressive symptoms and cognitive decline and MCI incidence among Chinese rural elderly individuals. Methods A 2-year follow-up study was conducted among 1,477 participants from the Anhui Healthy Longevity Survey (AHLS). Depressive symptoms were assessed by the 9-item Patient Health Questionnaire (PHQ-9), and cognitive status was evaluated by the Mini Mental State Examination (MMSE). Multivariable linear regression and logistic regression were employed. Results Every 1-unit PHQ-9 score increase was significantly associated with more cognitive decline (β = 0.157, 95% CI: 0.092, 0.221, p < 0.001) and a higher risk of MCI incidence (OR = 1.063, 95% CI: 1.025, 1.103, p = 0.001). The participants who experienced worsening of depression symptoms had a larger decline in the 2-year MMSE score (β = 0.650, 95% CI: 0.039, 1.261, p = 0.037) and elevated risks of incident MCI (OR = 1.573, 95% CI: 1.113, 2.223, p = 0.010). Limitations Screening tools rather than standard diagnostic procedures were used in the study. Moreover, the long-term associations still need further exploration since the follow-up time was short. Conclusions Increased depressive symptoms were associated with more cognitive decline and higher risks of incident MCI among Chinese rural residents.